The Role of 'Bundo Kanduang' Women's Group in Early Detection of High-Risk Pregnancy in Tanah Datar - Devi Syarief; Afrizal Afrizal; Delvi Hamdayani (Jurnal Bidan Cerdas, 2025)
Background: West Sumatra Province is the only region in Indonesia that adheres to the matrilineal system. An influential community leader in West Sumatra is the women's group 'Bundo Kanduang'. A preliminary study found an increase in problematic pregnancies in Tanah Datar District, West Sumatra. This study aims to determine the role of the 'Bundo Kanduang' women's group in efforts to increase knowledge, attitudes, and family roles in the early detection of high-risk pregnancies Method: This study used a quasi experiment pre-post test study design with control group design in Tanah Datar 2024. The population was the husband/family of pregnant women and the total sample was 22 people. Univariate analysis included frequency distribution of knowledge, attitude, and family role. Bivariate analysis used the Mann-Whitney U Test to analyze differences between the control and intervention groups. Results: There was an increase in knowledge scores and family roles in early detection of high-risk pregnancies. Statistical test results showed that there were differences in knowledge (0.001) and family roles (0.004) between the control and intervention groups with a p-value <0.05. Conclusion: The 'Bundo Kanduang' women's group has successfully improved knowledge and family roles. However, there was no significant difference in attitude, so further research is needed.